p-Toluenesulfonic Acid-Catalyzed Reaction of Phthalaldehydic Acids with Difluoroenoxysilanes: Access to 3-Difluoroalkyl Phthalides - Liu, Saimei; Li, Yan; Wang, Feiyi; Ma, Chao; Yang, Guichun; Yang, Jianguo; Ren, Jun (Synthesis, 2021)
A convenient approach for the synthesis of 3-difluoroalkyl phthalides has been developed from phthalaldehydic acids and difluoroenoxysilanes by using relatively inexpensive p-toluenesulfonic acid monohydrate (PTSA) as a catalyst. A series of 3-difluoroalkyl phthalides and cyclic difluoroalkyl ethers were obtained in up to 99% yield. The products obtained could be readily converted into difluoroalkyl phthalide derivatives by simple modifications.
Keywords: p-toluenesulfonic acid monohydrate; catalyst; phthalaldehydic acid; difluoroenoxysilane; 3-difluoroalkyl phthalide